Estágio supervisionado na Educação Especial: aplicação de um planejamento educacional individualizado - SILVA, Arlete Pereira da (2024)
Supervised internship is a crucial practical stage in Higher Education, helping many undergraduates define their area of affinity. In the Pedagogy course, supervised internship spans various areas, with a particular focus in this work on special education, from an inclusive perspective, emphasizing the application of an Individualized Educational Plan (IEP). One of the major challenges in Specialized Educational Assistance (SEA) is the development of the IEP, a fundamental plan for connecting activities between the SEA room and the regular classroom. In light of this, the issue arose: how can the internship contribute to the development of an IEP? The aim was to present a proposal for an individualized educational planning (IEP), carried out through the experince en the supervised internship in special education and identify the theoretical and methodological aspects that support the production of an IEP. Additionally, strategies for planning, execution, evaluation of the IEP were outlined, along with a proposal for the school. The IEP was successfully implemented with the assistance of the SEA teacher. It is emphasized that to work in education, it is necessary to constantly seek training and update the curriculum to provide students with higher quality and inclusive education.